Fungsi Hadits Nabi Muhammad SAW terhadap Al-Qur’an - Mukhyar Sani (UIN Antasari Banjarmasin, 2013)
The Qur'an is a holy book of Muslims, which contains the revelations of Allah. delivered to the Prophet Muhammad pbu. Its global content still needs clarity for people to be able to understand it properly. Prophet Muhammad pbu has authority to explain the unclear parts of the book through the Hadith or Sunnah. In this case, the books needs al-bayan, al-Tafsir al-tafshil, al-taqrir, perhaps even al-naskh derived from the prophet Muhammad pbu. He is acknowledged by the Qur'an as its